Profiling global diversity competence of Indonesian senior high students through the intercultural ukhuwah-based English instructional model - Rahma A. Rajak; Andi Nurwati; Titin Suhartini Kaaba (Journal of English Language Teaching and Learning (JETLE), 2026)
This study aimed to examine how global diversity competence was developed through an intercultural ukhuwah-based English instructional model and how students perceived its role in shaping their global competence in an Indonesian senior high school context. The concept of ukhuwah was positioned as an ethical perspective emphasizing relational solidarity, empathy, and social responsibility in intercultural learning. A qualitative case study design was employed, involving 25 eleventh-grade students across five learning stages: early introduction, ta’aruf, tafahum, ta’awun, and takaful. Data were collected through classroom observations, semi-structured interviews with five students, and document analysis, and were analyzed using a thematic approach. The findings indicated that indicators of global diversity competence emerged differently across stages. Awareness of cultural differences and initial intercultural communication appeared in the early introduction and ta’aruf stages, while deeper understanding and reflection on diversity were observed during tafahum. Collaborative engagement and empathetic interaction became more visible in ta’awun, and elements of social responsibility began to appear in takaful. Students also reported generally positive perceptions of the model, particularly in terms of increased confidence and intercultural awareness. The findings suggest that the model may support the early development of intercultural competence, although deeper competencies require more sustained and critical engagement.